Production of green biofuel by using a goat manure supported Ni–Al hydrotalcite catalysed deoxygenation process. Issue 3 (11th January 2019) - Zdainal Abidin, Shajaratun Nur; Lee, Hwei Voon; Juan, Joon Ching; Rahman, Noorsaadah Abd; Taufiq-Yap, Yun Hin
Abstract : Deoxygenation pathway of oleic acid to bio-hydrocarbon involves decarboxylation/decarbonylation of oxygen content from fatty acid structure in the form of carbon dioxide (CO2 )/carbon monoxide (CO), respectively, with the presence of goat manure supported Ni–Al hydrotalcite (Gm/Ni–Al) catalyst. Abstract : The high oxygen content in natural biomass resources, such as vegetable oil or biomass-pyrolysed bio oil, is the main constraint in their implementation as a full-scale biofuel for the automotive industry. In the present study, renewable fuel with petrodiesel-like properties was produced via catalytic deoxygenation of oleic acid in the absence of hydrogen (H2 ). The deoxygenation pathway of oleic acid to bio-hydrocarbon involves decarboxylation/decarbonylation of the oxygen content from the fatty acid structure in the form of carbon dioxide (CO2 )/carbon monoxide (CO), with the presence of a goat manure supported Ni–Al hydrotalcite (Gm/Ni–Al) catalyst. Goat manure is an abundant bio-waste, containing a high mineral content, urea as well as cellulosic fiber of plants, which is potentially converted into activated carbon. Synthesis of Gm/Ni–Al was carried out by incorporation of pre-activated goat manure (GmA) during co-precipitation of Ni–Al catalyst with 1 : 3, 1 : 1 and 3 : 1 ratios. The physico-chemical properties of the catalysts were characterized by X-ray diffractometry (XRD), Brunauer–Emmet–Teller (BET) surface area, field emission surface electron microscopy (FESEM) and temperature program desorption ammonia (TPD-NH3 ) analysers. The catalytic deoxygenation reaction was performed in a batch reactor and the product obtained was characterized by using gas chromatography-mass spectroscopy (GCMS) for compound composition identification as well as gas chromatography-flame ionisation detector (GC-FID) for yield and selectivity determination. The optimization and evaluation were executed using response surface methodology (RSM) in conjunction with central composite design (CCD) with 5-level-3-factors. From the RSM reaction model, it was found that the Gm/Ni–Al 1 : 1 catalysed deoxygenation reaction gives the optimum product yield of 97.9% of hydrocarbon in the range of C8 –C20, with diesel selectivity (C17 : heptadecane and heptadecene compounds) of 63.7% at the optimal reaction conditions of: (1) reaction temperature: 327.14 °C, (2) reaction time: 1 h, and (3) catalyst amount: 5 wt%.